Image Enhancement and Modification Application Using Sharpening, Grayscale, and Additional Visual Effects on Android - Prayugo, Riko Prananda; Gibran, M. Khalil; Akbar, Mukhamad Rizky; Wahyudi, Andika (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The development of photographic technology on Android devices has increased the frequency of digital image usage in various sectors, such as social media, education, documentation, and other visual needs. However, the quality of the images produced is sometimes not as expected. Issues such as lack of sharpness, inconsistent lighting, and less visually appealing displays still frequently occur. Therefore, this research aims to create an Android-based application that can enhance and modify the quality of digital images through sharpening, grayscale, and several additional visual effects. The sharpening method is applied to improve image clarity and emphasize edge details of objects in the image, while grayscale conversion is useful for transforming color images into grayscale images that are more concise yet still informative. In addition, this application is equipped with extra visual effect features such as sepia, as well as brightness, contrast, and blur adjustments, enabling users to customize the image appearance according to their aesthetic and visual quality needs. The application is developed using the Java programming language and implemented in Android Studio. The test results show that this application is able to enhance image clarity, improve visual aspects, and provide various effects similar to those found in modern image editing applications. Therefore, this application can serve as a practical, effective, and easy-to-use tool for enhancing and modifying the quality of Android-based digital images.